2019
DOI: 10.1016/j.esxm.2019.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Female Sexual Function: Risk Factors for Postpartum Sexual Dysfunction

Abstract: Introduction: Women's sexual health is a vital and important part of life at any age. In particular, pregnancy and childbirth bring biological, psychological, and social changes which may influence sexual health. It has been shown that sexual function declines during pregnancy and does not return to its baseline levels during the postpartum period. Despite the complexity and significance of this subject, health providers often neglect sexual aspects during pregnancy and postpartum. Aim: We believe that clarify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
65
1
29

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(103 citation statements)
references
References 46 publications
8
65
1
29
Order By: Relevance
“…Hence, pelvic oor training cannot completely compensate the anatomical defect set by a CAV, but maybe can improve the extent and rate of prolapse in this group. 85-91% of women had sexual intercourse 6-9 months after birth, which is comparable with other studies showing that 89% of women resume sexual activity within 6 months of giving birth (30). Of those women, 60-83% reported an unchanged situation regarding sexual satisfaction.…”
Section: Assessment Of Women`s Complaints 1-4 Days After Birth (P1)supporting
confidence: 81%
See 1 more Smart Citation
“…Hence, pelvic oor training cannot completely compensate the anatomical defect set by a CAV, but maybe can improve the extent and rate of prolapse in this group. 85-91% of women had sexual intercourse 6-9 months after birth, which is comparable with other studies showing that 89% of women resume sexual activity within 6 months of giving birth (30). Of those women, 60-83% reported an unchanged situation regarding sexual satisfaction.…”
Section: Assessment Of Women`s Complaints 1-4 Days After Birth (P1)supporting
confidence: 81%
“…Other studies report that sexual function after birth is not altered by pelvic oor muscle strength or mode of delivery, but by the presence of high-grade perineal tears (30,32,33). The association of sexual function and satisfaction to the presence of a LAM avulsion remains controversial (29,34).…”
Section: Assessment Of Women`s Complaints 1-4 Days After Birth (P1)mentioning
confidence: 99%
“…Similarly, Gutzeit et al showed that delivery mode had no significant effect on short-and long-term SF. Furthermore, episiotomy did not have a favorable impact on the women's sexual performance, whereas breastfeeding was found to have a little unfavorable impact on women's SF [18]. A meta-analytical study also confirms the finding [19].…”
Section: Discussionsupporting
confidence: 55%
“…When data between breastfeeding and non-breastfeeding women are compared, the results show that those who are breastfeeding are more likely to experience pain during intercourse and poor vaginal lubrication 6 , 15 . A possible justification for the low vaginal lubrication in breastfeeding women can be the physiological absence of the estrogen hormone during breastfeeding 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Considering the variety of existing assessment methods, there is international consensus that the prevalence of female dysfunction, regardless of age, is 40% to 50% 2 , 5 . When considering the pregnant puerperal cycle, recent studies show a high prevalence of sexual dysfunction ranging from 41% to 83% in the first three months 6 and around 60% in the first postpartum year 3 , 7 .…”
Section: Introductionmentioning
confidence: 99%